Pengaruh Biaya Promosi Terhadap Peningkatan Dana Pihak Ketiga (Studi Kasus PT Bank Muamalat KCP Binjai) - Waqqosh, Abi (TIN: Terapan Informatika Nusantara, 2020)
This study uses quantitative methods. which uses numbers in data presentation and analysis using statistical tests. The data analysis used in this research is simple regression analysis. This study aims to determine the effect of promotional costs on increasing third party funds at PT Bank Muamalat KCP Binjai. From the research results, the results of the Regression and Correlation Test can be concluded that the promotion cost has a significant effect on the amount of third party funds. which is significant to variable Y (amount of third party funds). With the F table value of 4.67, or fcount (6.703)> ftable (4.67), it can be concluded that the F test is significant, which means that collectively the independent variable (the amount of promotional costs) affects the dependent variable (the amount of third party funds). Obtained R Square value of 0.583Â² = 0.34 X 100% = 34%. This means that the amount of third party funds is influenced by the amount of promotional costs by 34% and the remaining 66% is influenced by other variables besides promotional cost services. amount of third party funds. Due to count (2.587)> than t table (1.771), Ho is rejected and H1 is accepted, which means that there is a positive relationship between the variable promotion cost and the amount of third party funds. For the purposes of interpreting the calculation results of the correlation coefficient of 0.583, the relationship is moderate or strong. Based on these results it is known that the variable X (the amount of promotion costs) has an effect of 33.89% on the amount of third party funds and the remaining 66.11% is influenced by factors other services outside the promotion fee